Current state of vascular access in Singapore. Issue 5 (September 2020) - Pang, Suh Chien; Tan, Ru Yu; Kwek, Jia Liang; Lee, Kian Guan; Foo, Marjorie Wai Yin; Choong, Lina Hui Lin; Chong, Tze Tec; Tan, Chieh Suai
This article described the current state of vascular access management for patients with end-stage renal disease in Singapore. Over the past 10 years, there has been a change in the demographics of end-stage renal disease patients. Aging population and the increase in prevalence of diabetes mellitus has led to the acceleration of chronic kidney disease and increase in incidence and prevalence of end-stage renal disease. Vascular access care has, therefore, been more complicated, with the physical, psychological, and social challenges that occur with increased frequency in elderly patients and patients with multiple co-morbidities. Arteriovenous fistula and arteriovenous graft are created by vascular surgeons, while maintenance of patency of vascular access through endovascular intervention has been a shared responsibility between surgeons, interventional radiologists, and interventional nephrologists. Pre-emptive access creation among end-stage renal disease patients has been low, with up to 80% of new end-stage renal disease patients being commenced on hemodialysis via a dialysis catheter. Access creation is exclusively performed by a dedicated vascular surgeon with arteriovenous fistula success rate up to 78%. The primary and cumulative patency rates of arteriovenous fistula and arteriovenous graft were consistent with the results from many international centers. Vascular access surveillance is not universally practiced in all dialysis centers due to its controversies, in addition to the cost and the limited availability of equipment for surveillance. Timely permanent access placement, with reduced dependence on dialysis catheters, and improved vascular access surveillance are the main areas for potential intervention to improve vascular access management.